Human Activity Behind the Unprecedented 2020 Wildfire in Brazilian Wetlands (Pantanal) - de Magalhães Neto, Newton; Evangelista, Heitor (Frontiers in Environmental Science, 2022)
The Pantanal natural region in South America is the largest wetland worldwide. Due to floods and a diverse lithology, this wetland area exhibits high plant and animal biodiversity levels and encompasses more than 185,000 km2. In 2020, the Pantanal experienced the worst recorded fire episode in history. Hundreds of thousands of hectares burned, threatening habitats and corre-sponding ecosystem functions. The fire reached regions never burned before, including national conservation units. Although federal authorities have blamed climate change and cultural in-digenous practices, environmentalists, scientists, and non-governmental organizations have questioned this foregone conclusion. To better understand this historical event, we examined the burn severity in conservation units most affected by fire and the association with human and climate factors (represented by the fire occurrence distance to roads/waterways/railways and drought severity, respectively) and analyzed fire spatial patterns and durations. Via a comparison of these two factors, we demonstrated that 60% of the fire outbreaks was concentrated at distances less than 5 kilometers from roads, waterways, and railways and that 80% was concentrated at distances less than 10 kilometers from areas with human activities. Since values of the SPEI (drought index) < -2.6 were critical to the spread of fire, a combination of more favorable climate conditions enabled the rapid and irreversible spread of fire. The observed association between fire occurrence and distance to roads makes the ongoing plans for road expansion of great concern, considering the 2020 fire episode, which greatly affected natural vegetation and conservation units across the Pantanal. The determination of trends in fire hot spot regions in the Pantanal can help environmental surveillance and fire control.